The NOTCH pathway contributes to cell fate decision in myelopoiesis - Bugeon, Laurence (Ferrata Storti Foundation, 2011)
BACKGROUND: Controversy persists regarding the role of Notch signaling in myelopoiesis. We have used genetic approaches, employing two Notch zebrafish mutants deadly seven (DES) and beamter (BEA) with disrupted function of notch1a and deltaC, respectively, and Notch1a morphants to analyze the development of leukocyte populations in embryonic and mature fish. DESIGN AND METHODS: Myelomonocytes were quantified in early embryos by in situ hybridization using a myeloper-oxidase (mpx) probe. Morpholinos were used to knock down expression of Notch1a or DeltaC. Wound healing assays and/or flow cytometry were used to quantify myelomonocytes in 5-day post-fertilization (dpf) Notch mutants (BEA and DES), morphants or pu.1:GFP, mpx:GFP and fms:RFP transgenic embryos. Flow cytometry was performed on 2–3 month old mutant fish. RESULTS: The number of mpx(+) cells in embryos was reduced at 48 hpf (but not at 26 hpf) in DES compared to WT. At 5 dpf this was reflected by a reduction in the number of myelomonocytic cells found at the wound site in mutants and in Notch1a morphants. This was due to a reduced number of myelomonocytes developing rather than a deficit in the migratory ability since transient inhibition of Notch signaling using DAPT had no effect. The early deficit in myelopoiesis was maintained into later life, 2–3 month old BEA and DES fish having a decreased proportion of myelomonocytes in both the hematopoietic organ (kidney marrow) and the periphery (coelomic cavity). CONCLUSIONS: Our results indicate that defects in Notch signaling affect definitive hematopoiesis, altering myelopoiesis from the early stages of development into the adult.